Tesawalamai : protection of community rights or discrimination of women? - Satkunanathan, Ambika (Colombo : Social Scientists' Association, 2004)
Legal aspects with reference to Sri Lankan women; a study.
Keywords: Women -- Legal status, laws, etc. -- Sri Lanka; Customary law -- Sri Lanka